Hospital-treated deliberate self-poisoning patients: Drug-induced delirium and clinical outcomes. (February 2022) - Gale, Lindsay; McGill, Katie; Twaddell, Scott; Whyte, Ian M; Lewin, Terry J; Carter, Gregory L
Objective: Drug-induced delirium has been attributed to opioid, benzodiazepine, antipsychotic, antihistaminic and anticholinergic drug groups at therapeutic doses. Delirium also occurs in hospital-treated self-poisoning (at supra-therapeutic doses), although the causative drug classes are not well established and co-ingestion is common. We tested the magnitude and direction of association of five major drug groups with incident cases of delirium. Methods: A retrospective longitudinal cohort ( n = 5131) study was undertaken of deliberate and recreational/chronic misuse poisoning cases from a regional sentinel toxicology unit. We described ingestion and co-ingestion patterns and estimated the unadjusted and adjusted odds for developing a drug-induced delirium. We also estimated the odds of drug-induced delirium being associated with three outcomes: intensive care unit admission, general hospital length of stay and discharge to home. Results: Drug-induced delirium occurred in 3.9% of cases ( n = 200). The unadjusted odds ratios for development of delirium were increased for anticholinergics 10.79 (5.43–21.48), antihistamines 6.10 (4.20–8.84) and antipsychotics 2.99 (2.20–4.06); non-significant for opioids 1.31 (95% confidence interval = [0.81, 2.13]); and reduced for benzodiazepines 0.37 (0.24–0.58); with little change after adjustment for age, gender and co-ingestion. Delirium was associated with intensive care unit admission, longer length of stay and discharge destination. Conclusion: Drug-induced delirium was uncommon in this population. Co-ingestion was common but did not alter the risk. In contrast to drug-induced delirium at therapeutic doses in older populations, opioids were not associated with delirium and benzodiazepines were protective. Drug-induced delirium required increased clinical services. Clinical services should be funded and prepared to provide additional supportive care for these deliriogenic drug group ingestions.